The Effect of Lack Unconscious Learning to Speak English Fluently - Shanshoup, Maryam Ali; Al-rubshi, Samir; Sousy, Sabreen Abo baker; Al Tounsy, Salima Faraj (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Mastering speaking skill is one of the most important aspects of learning a second or foreign language. This research sought to discover the reasons behind student's inability to have speaking skill, the role of unconscious learning in speaking English language and finding the practical solution. The paper shows some previous studies and theories of researches that are associated with our research study and probable declare our hypothesis. The current study used two methods that are questionnaire and interview that are directed to a sample of 75 Libyan female students who were selected from Alasmarya Islamic University. The data analyzed using SPSS Program. The findings of this study showed that most of students of Alasmarya Islamic University failed in speaking English fluently, because of several factors that influenced these difficulties like: insufficient time and lack of activities, students have no idea about the topic, and overuse memorization, imbalance between listening and speaking lectures, and unqualified curriculums. The study's overall process is concluded in the final chapter. It is concerned with the answers to the research questions posed in the first chapter, as well as the results; the report also provides suggestions for teachers, and students to adopt. The research recommends: increase the time of listening and speaking lecture, increase the practical part, and teachers may take in their account that curriculums should not be crowded with old theories.
Keywords: Speaking; Unconscious; Problem; Lack; Alasmarya